2004
DOI: 10.1007/s00167-004-0524-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of chronic, unreduced posterior dislocation of the shoulder

Abstract: Four patients with chronic posterior dislocation of the shoulder underwent surgical treatment after an average delay of 10 months from injury. They were examined clinically and radiographically at an average follow-up of 32 months. Treatment consisted of subscapularis tendon transfer (McLaughlin procedure) into the humeral defect in one case, transfer of the lesser tuberosity (McLaughlin modified procedure) in two cases, and in the fourth case-a patient with a 19-month missed dislocation and 50% humeral head l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…However, there is also evidence of good results with a later diagnosis with a great functional improvement. In particular, a study of 2005 [18] showed a case of neglected posterior shoulder dislocation, which underwent surgery with a delay of 19 months, having an optimal functional recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is also evidence of good results with a later diagnosis with a great functional improvement. In particular, a study of 2005 [18] showed a case of neglected posterior shoulder dislocation, which underwent surgery with a delay of 19 months, having an optimal functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In a major defect, the Neer technique (also known as the modified McLaughlin procedure) proposes the detachment of the subscapularis through an osteotomy and a fixation with cancellous screws [11]. Both techniques are effective in acute and neglected dislocations [17,18]. In smaller bone defects, it is possible to transfer a plication of the subscapularis tendon and to fix it through arthroscopic suture anchors [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Allograft reconstruction is preferable to arthroplasty in larger defects in relatively younger patients (Table I). [1,[7][8][9][10][11][12][13][14] For patients who have good bone quality of the residual head and an absence of relevant osteoarthrosis, reconstruction with an allograft represents a viable alternative to hemiarthroplasty or total joint arthroplasty for carefully selected larger defects. However, our follow-up time was too short to recommend whether avascular necrosis or graft collapse would develop, since posterior bilateral dislocation was usually experienced by middle-aged active males.…”
Section: Discussionmentioning
confidence: 99%
“…Dislocation is associated almost always with a reverse Hill-Sachs lesion (an impression defect of anteromedial aspect of the humeral head, also mentioned as ''inverted Hill-Sachs'' or ''McLaughlin'' lesion) [11] and probably with fractures of the posterior aspect of the glenoid rim, fractures of the greater/lesser tuberocity, lesions of the anterior capsule and the subscapularis tendon. Accurate physical examination and radiological evaluation by lateral scapular view or, if tolerated by the patient, by axillary view, in addition to the standard anteroposterior view, are mandatory to reveal the injury [2,8].…”
Section: Discussionmentioning
confidence: 99%